Socio-economic and age variations in response to supermarket-led checkout food policies: a repeated measures analysis - Katrine Ejlerskov (International Journal of Behavioral Nutrition and Physical Activity, 2018)
Abstract Background Dietary inequalities between population groups are common with older and more affluent individuals tending to have healthier diets. Differential responses to health interventions may exacerbate inequalities. Changing what foods are displayed at supermarket checkouts is one intervention that has the potential to change diets. The aim of this study was to assess whether differences in purchases of common checkout foods from supermarkets with different checkout food policies varied according to age group and social grade. Methods We analysed annual household purchase data for 2013–17 from nine leading UK supermarkets, split according to age of the main household shopper and household social grade. Checkout food policies were categorised as clear and consistent, vague or inconsistent, and none. Policies were heterogeneous but all included removal of confectionery and/or chocolate from checkouts. Mixed effects linear regression models were used to assess differences in purchases of common checkout foods (sugary confectionery, chocolate and potato crisps) by checkout food policy and whether these varied by age group or occupational social grade. Results Relative to supermarkets with no checkout food policy, 14% (95% CI: 4–22%) fewer purchases of common checkout foods per household per percentage market share were made in supermarkets with a clear and consistent policy. Adjusted mean numbers of purchases were higher in older age groups than the youngest, but there were no differences between the highest and other social grades. There were significant interactions between checkout food policy and both age group and social grade. In supermarkets with clear and consistent policies, 23% (6–36%), 20% (2–34%), and 23% (7–37%) fewer purchases were made in age groups 45–54, 55–64 and 65+ years respectively, compared to all groups combined. In supermarkets with clear and consistent policies, there were 21% (4–35%), 26% (9–39%) and 21% (3–35%) fewer purchases made by households in the highest two and lowest social grades respectively, compared to all groups combined. Conclusions Households with older main shoppers and those in the most and least affluent social grades may be most responsive to supermarket checkout food policies. As older and more affluent groups tend to have healthier diets overall, it is unlikely that supermarket checkout food policies contribute to greater dietary equity.